TIPOLOGI DAN DINAMIKA PONDOK PESANTREN - Andry Setiawan; Ani Fatimah Zahra Saifi; Euis Komala; Erni Susilawati; Deden Kurnia Adam (Pusat Penelitian dan Pengabdian (P3M) STKIP Majenang, 2025)
The development of the world, particularly in information technology, has brought about changes in all aspects of life, including social structures, culture, and educational systems, including Islamic boarding schools (pesantren). The changes or modernization of Islamic education in Indonesia, related to the idea of Islamic modernization, have influenced the dynamics of knowledge in the pesantren environment, resulting in the emergence of various types of pesantren and their respective dynamics in responding to modernization. This research aims to analyze the typology and dynamics of pesantren using a qualitative approach and descriptive method in the form of library research. There are at least three types of pesantren discussed in this study: traditional pesantren (salaf), modern pesantren (khalaf), and convergence pesantren (a mix of salaf and khalaf), also referred to as semi-modern. These three types of pesantren illustrate the dynamics of Islamic education in Indonesia, striving to balance tradition and modernity. The salaf pesantren preserves classical Islamic values, the khalaf pesantren responds to the needs of the modern world, while the convergence pesantren seeks to integrate both so that students possess balanced religious and general competencies. The greatest challenge for all three is how to remain relevant to the times without sacrificing the essence of religious values